SALL2 represses cyclins D1 and E1 expression and restrains G1/S cell cycle transition and cancer‐related phenotypes. Issue 7 (21st May 2018) - E. Hermosilla, Viviana; Salgado, Ginessa; Riffo, Elizabeth; Escobar, David; Hepp, Matías I.; Farkas, Carlos; Galindo, Mario; Morín, Violeta; García‐Robles, María A.; Castro, Ariel F.; Pincheira, Roxana
Abstract : SALL2 is a poorly characterized transcription factor that belongs to the Spalt‐like family involved in development. Mutations on SALL2 have been associated with ocular coloboma and cancer. In cancers, SALL2 is deregulated and is proposed as a tumor suppressor in ovarian cancer. SALL2 has been implicated in stemness, cell death, proliferation, and quiescence. However, mechanisms underlying roles of SALL2 related to cancer remain largely unknown. Here, we investigated the role of SALL2 in cell proliferation using mouse embryo fibroblasts (MEFs) derived from Sall2 −/− mice. Compared to Sall2 + / + MEFs, Sall2 − / − MEFs exhibit enhanced cell proliferation and faster postmitotic progression through G1 and S phases. Accordingly, Sall2 −/− MEFs exhibit higher mRNA and protein levels of cyclins D1 and E1. Chromatin immunoprecipitation and promoter reporter assays showed that SALL2 binds and represses CCND1 and CCNE1 promoters, identifying a novel mechanism by which SALL2 may control cell cycle. In addition, the analysis of tissues from Sall2 +/+ and Sall2 − / − mice confirmed the inverse correlation between expression of SALL2 and G1‐S cyclins. Consistent with an antiproliferative function of SALL2, immortalized Sall2 − / − MEFs showed enhanced growth rate, foci formation, and anchorage‐independent growth, confirming tumor suppressor properties for SALL2. Finally, cancer data analyses show negative correlations between SALL2 and G1‐S cyclins' mRNA levels in several cancers. Altogether, our results demonstrated that SALL2 is a negative regulator of cell proliferation, an effect mediated in part by repression of G1‐S cyclins' expression. Our results have implications for the understanding and significance of SALL2 role under physiological and pathological conditions. Abstract : SALL2 inhibits cell proliferation by repressing G1‐to S‐phase cell cycle transition. This effect of SALL2 is associated with the transcriptional repression of cyclins D1 and E1.